2018
DOI: 10.14814/phy2.13889
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the nitric oxide pathway of the pulmonary vasculature after exposure to hypoxia in swine model of neonatal pulmonary vascular disease

Abstract: Neonatal pulmonary vascular disease (PVD) is increasingly recognized as a disease that complicates the cardiopulmonary adaptations after birth and predisposes to long‐term cardiopulmonary disease. There is growing evidence that PVD is associated with disruptions in the nitric oxide (NO)‐cGMP‐phosphodiesterase 5 (PDE5) pathway. Examination of the functionality of different parts of this pathway is required for better understanding of the pathogenesis of neonatal PVD. For this purpose, the role of the NO‐cGMP‐PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
(157 reference statements)
0
1
0
Order By: Relevance
“…Moreover, PDE5 induction in the PPHN lamb model has been linked to mitochondrial oxidative stress with rapid increases in mitochondrial ROS and PDE5 activity within 30 minutes of hyperoxia exposure (103). Similarly, PDE5 activation and impairments in cGMP production have been reported in other neonatal models associated with increased oxidative stress, including a swine model of hypoxia-induced pulmonary vascular disease and a neonatal mouse model of HLI (66,104), as well as in mice with chronic heart failure (70). Findings from animal models of PPHN also demonstrated that increased oxidative stress reduced the bioavailability of NO through eNOS uncoupling and downregulation of eNOS expression and function (101,105,106).…”
Section: Antioxidantsmentioning
confidence: 93%
“…Moreover, PDE5 induction in the PPHN lamb model has been linked to mitochondrial oxidative stress with rapid increases in mitochondrial ROS and PDE5 activity within 30 minutes of hyperoxia exposure (103). Similarly, PDE5 activation and impairments in cGMP production have been reported in other neonatal models associated with increased oxidative stress, including a swine model of hypoxia-induced pulmonary vascular disease and a neonatal mouse model of HLI (66,104), as well as in mice with chronic heart failure (70). Findings from animal models of PPHN also demonstrated that increased oxidative stress reduced the bioavailability of NO through eNOS uncoupling and downregulation of eNOS expression and function (101,105,106).…”
Section: Antioxidantsmentioning
confidence: 93%